Wpływ patologii rodzinnej na kształtowanie postaw antyspołecznych czternasto- i piętnastolatków - Wilczyński, Maciej (Problemy Prawa Karnego, 2025)
The aim of the article is to analyze the influence of pathologies occurring in the family on the criminogenic behavior of young people. The starting point is the assumption that the family environment plays a crucial role in shaping children’s attitudes. The study used a diagnostic survey method – an online survey was conducted among students of the 7th and 8th grades of primary schools. The results indicate that domestic violence, addictions (alcohol, drugs) and parental unemployment have a significant relationship with the manifestations of demoralization among young people. Students from dysfunctional families are more likely to exhibit aggressive behavior, break social norms, and have behavioral problems. The conclusions of the study confirm previous literature findings. It is necessary to involve schools, especially teachers, in preventive activities and support for children from families that are at risk of pathology.